Unraveling the mechanical behaviour of hydrazine borane (NH2–NH2–BH3). Issue 4 (12th January 2018) - Yot, Pascal G.; Yadav, Vibhav; Ould Amara, Salem; Itiè, Jean-Paul; Demirci, Umit B.; Maurin, Guillaume
Abstract : The structural behaviour of hydrazine borane was explored under mechanical stimulus. The compressibility of this solid was established to be relatively low and highly anisotropic. The mechanical response was correlated to the pressure-induced changes of its crystal structure in terms of intra- and inter-molecular bond lengths and angles parameters. Abstract : Crystalline B–N–H compounds of low molecular weight have been intensively investigated over the past two decades owing to their promises for chemical hydrogen storage. Hydrazine borane NH2 –NH2 –BH3 is one of the most recent examples of this family of materials. In the present work, we explored its structural behaviour under mechanical stimulus by synchrotron high pressure X-ray diffraction. It has been evidenced that hydrazine borane shows a gradual pressure-induced decrease of its unit cell dimension and the process is reversible when the applied pressure is released. The compressibility of this material was established to be relatively low (high bulk modulus) and highly anisotropic. As revealed by molecular simulations based on Density Functional Theory calculations, the mechanical behaviour of NH2 –NH2 –BH3 was correlated to the pressure-induced changes of its crystal structure in terms of intra- and intermolecular bond lengths and angles parameters.